Ultrasound as a Method to Control Protein-Polysaccharide Foam Stability by Microscopic Parameter Alteration - Martínez, Karina Dafne (2014)
The objective of this work was to determine the effect of ultrasound application on the stability of foams of mixed systems of soy protein isolate and a hydroxypropyl methylcellulose called E4M at pH 7 and 3. It was used a soluble fraction of soy protein which is the responsible of functional properties in food applications. The pHs selected were used according to normally range in food meals. The samples were sonicated for 20 min using an ultrasonic processor Vibra Cell Sonics model VCX 750 at a frequency of 20 kHz and an amplitude of 20%. The foams were produced using a foaming instrument with a second CCD camera. The relative foam conductance (Cf%) and complementary parameters: half-life time, t½; relaxation times corresponding to the kinetics of liquid drainage, td; and disproportionation and collapse, tdc, were obtained. Significant differences were found for the relaxation times td and tdc at pH 7 as a consequence of the ultrasound treatment. It could be seen that ultrasound promoted a great increment of these relaxation times in these conditions, attributed to quantity of proteins at different pH.